2023
DOI: 10.1002/dev.22394
|View full text |Cite
|
Sign up to set email alerts
|

Maternal negative affect moderates behavioral and physiological synchrony in Latinx and Black mother–child dyads

Abstract: Positive behavioral synchrony (PBS) between mothers and children involves the bidirectional exchange of verbal and nonverbal communication. Respiratory sinus arrhythmia (RSA) synchrony reflects the concordance between mother-child physiological states. Both PBS and RSA synchrony can be undermined by psychopathology symptoms. Latinx and Black families may experience contextual stressors that contribute to heightened symptoms of psychopathology, yet minimal research has examined relations between psychopathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 151 publications
(234 reference statements)
0
0
0
Order By: Relevance
“…A plethora of literature has linked emotional instability with elevations in psychopathology symptoms (Houben et al, 2015;Sperry & Kwapil, 2022;Sperry et al, 2020), and our findings provide preliminary evidence for the relation between depressive symptoms and RSA instability in mothers. Research demonstrates that mothers experiencing internalizing symptoms may exhibit physiological and emotional dysregulation (Hale et al, 2023;Han et al, 2016;Lunkenheimer et al, 2018;Somers et al, 2021). Literature also posits that dynamic fluctuations in RSA may reflect adaptive engagement with one's environment and indicate flexible responding to contextual stressors (Grossman & Taylor, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A plethora of literature has linked emotional instability with elevations in psychopathology symptoms (Houben et al, 2015;Sperry & Kwapil, 2022;Sperry et al, 2020), and our findings provide preliminary evidence for the relation between depressive symptoms and RSA instability in mothers. Research demonstrates that mothers experiencing internalizing symptoms may exhibit physiological and emotional dysregulation (Hale et al, 2023;Han et al, 2016;Lunkenheimer et al, 2018;Somers et al, 2021). Literature also posits that dynamic fluctuations in RSA may reflect adaptive engagement with one's environment and indicate flexible responding to contextual stressors (Grossman & Taylor, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent systematic review concluded that during distressing dyadic tasks (e.g., puzzle task), parents with greater parasympathetic nervous system responding demonstrated higher rates of unsupportive parenting behaviors when compared to parents with less physiological reactivity (Badovinac & colleagues et al, 2023). Prior work also demonstrates that mothers with fewer internalizing symptoms and more supportive parenting behaviors (e.g., parental warmth, validation, sensitivity) display higher levels of RSA suppression (i.e., greater decrease from baseline to stress task) compared to mothers with more symptoms and fewer supportive behaviors (Eisenberg et al, 2012;Fuchs et al, 2021;Hale et al, 2023;Perry et al, 2012). Taken together, findings suggest that the links between maternal physiological responding and supportive parenting behaviors are still being explored, likely varying across developmental timepoints and environmental contexts.…”
Section: Physiological Copingmentioning
confidence: 99%
See 1 more Smart Citation